Li-ion transport mechanisms in Ge/Cl dual-doped Li10GeP2S12 solid electrolytes: Synergistic insights from experimental structural characterization and machine-learning-assisted atomistic modeling - Choi, Yong-Seok; Jeong, Jiwon; Lee, Youngin; Ahn, Hyuna; Scanlon, David O.; Chung, Kyung Yoon; Lee, Jae-Chul (Wiley, 2024)
Enhancing the ionic conductivity of sulfide solid electrolytes (SEs) through dual-doping is a well-established approach, yet the atomic-level mechanisms driving these improvements remain elusive. By dual-doping Ge and Cl into the Li10GeP2S12 (LGPS) framework, we synthesized Ge/Cl-doped LGPS (Li10+xGe1+2xP2-2xS12-xClx, x = 0.3) with an ionic conductivity of 12.4 mS/cm at 25 degrees C, a value that stands among the highest for LGPS-type SEs. This achievement emphasizes the pivotal role of dopant selection in modulating Li-ion transport mechanisms, thereby enhancing SE performance. Our research elucidates the intricate atomic mechanisms responsible for this enhanced ionic conductivity, with a particular focus on the synergistic effects of Ge and Cl dual-doping. Integrating advanced multianalytical techniques, including experiments and atomistic modeling (machine-learning-assisted molecular dynamics simulations and density functional theory calculations), we provide comprehensive insights into the structure-property relationship in Ge/Cl-doped LGPS SEs. Our findings reveal that Cl doping significantly enhances the paddle-wheel dynamics, while Ge doping promotes cooperative Li diffusion through the formation of Li interstitials. This dual-doping approach not only elucidates the structural and functional dynamics of SEs but also paves the way for designing dopants to enhance ionic conductivity. The insights gained from this study offer a strategic direction for developing higher-performance SEs, highlighting the importance of tailored dopant selection in advancing energy storage technologies.